MASCULINITY REFLECTED BY WOMAN MAIN CHARACTERS IN CHARLES DICKEN’S GREAT EXPECTATION AND ITS CONTRIBUTION TO TEACHING PROSE AND DRAMA - Fernando Setyo Nugroho; Nur Hidayat (ETERNAL (English Teaching Journal), 2013)
The objective of the study are to find out: (1) 1. Masculine elements are reflected in the novel of Great Expectation (2003)? (2) how Great Expectations novel can contribute to Prose and Drama teaching.The research design of this final project is qualitative since it just collects the data and draws conclusions based on the analysis of the data. The research concerns in identifying, analyzing and making conclusion. The method of collecting data is analysis content of movie and novel. The data was taken by Great Expectations movie and novel by Charles Dicken.The research shows that Great Expectations novel has some masculine element in its content. The masculine elements found, such as: Appearance, Character, Attitude, Speech, Language. In contribution to Prose and Drama teaching, this study can be used as a source of teaching material. There are many media, especially novel. It is explained in this study. It is useful to reader or learner in comprehending the way to analyze the element of masculinity and appreciating literary work.The application of this final project by the masculinity element of Great Expectations novel will help the teacher, student and reader in exploring, revising, completing their capability about the characterization in classroom interaction, especially in Prose and Drama. So, the teaching and learning process will be deeper.